2022
DOI: 10.1002/admi.202101278
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Atomic Layer Deposition of P‐Type SnO Thin Film Transistors Using Tin(II)bis(tert‐amyloxide)

Abstract: interface engineering, in addition to effective doping strategies involving scalable and highly precise processing technology on large areas, have been deemed necessary to advance the development of p-type oxide materials. [5] Atomic layer deposition (ALD) is a layerby-layer thin film deposition method that allows for atomic-level control over thickness and material/interface properties, resulting in conformal and uniform deposition over large areas, and high aspect ratio substrates. [9,10] Such unique feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…In spatial mode, the ALD precursor and co-reactant are continuously dosed on a reciprocating or rotating substrate, and no extensive chamber-purge steps are needed to keep the precursor and co-reactant from reacting in the gas-phase (CVD-like reaction). Therefore much shorter ALD cycle times can be achieved [14]. Most of the literature on spatial ALD concerns metal oxides produced either by thermal or plasma-enhanced spatial ALD, [4,[15][16][17] and only a few examples have been published for spatial-ALD of metallic films (Ag and Cu) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In spatial mode, the ALD precursor and co-reactant are continuously dosed on a reciprocating or rotating substrate, and no extensive chamber-purge steps are needed to keep the precursor and co-reactant from reacting in the gas-phase (CVD-like reaction). Therefore much shorter ALD cycle times can be achieved [14]. Most of the literature on spatial ALD concerns metal oxides produced either by thermal or plasma-enhanced spatial ALD, [4,[15][16][17] and only a few examples have been published for spatial-ALD of metallic films (Ag and Cu) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the feasibility of p-type conductivity in SnO has been experimentally demonstrated using several techniques, including reactive magnetron sputtering, ,, atomic layer deposition, , pulsed laser deposition, ,, e-beam evaporation, ,, and solution process. , However, the performance of the prepared SnO still varies greatly depending on the type of sample and the resulting crystal structure. For bulk SnO polycrystals, a hole mobility as high as 30.0 cm 2 V –1 s –1 has been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Yet, this aspect needs to be addressed in order for the p-type oxides to be technologically commensurate with their n-type counterparts. 4 To date, the feasibility of p-type conductivity in SnO has been experimentally demonstrated using several techniques, including reactive magnetron sputtering, 14,15,20 atomic layer deposition, 5,21 pulsed laser deposition, 10,12,22 e-beam evaporation, 6,23,24 and solution process. 13,25 However, the performance of the prepared SnO still varies greatly depending on the type of sample and the resulting crystal structure.…”
Section: Introductionmentioning
confidence: 99%
“…25 Recently, Mameli et al reported a high-throughput spatial ALD process for SnO using tin(II) bis(tert-amyloxide) ([Sn(TAA) 2 ]) and water with GPC values of 0.09 Å to 0.55 Å. 26 It is thus apparent that the choice of the precursor is crucial for the successful process development and process characteristics of SnO films. Rational design of the precursor ligand sphere can significantly tune physicochemical parameters like reactivity, volatilization temperature (T vol ) and aggregation state and can be tailored towards the desired properties for the respective processes.…”
Section: Introductionmentioning
confidence: 99%
“…25 Recently, Mameli et al reported a high-throughput spatial ALD process for SnO using tin( ii ) bis( tert -amyloxide) ([Sn(TAA) 2 ]) and water with GPC values of 0.09 Å to 0.55 Å. 26…”
Section: Introductionmentioning
confidence: 99%